Design and analysis of pumpjet propulsors using CFD-based optimization. (1st June 2023) - Gaggero, Stefano; Martinelli, Mattia
Abstract: The design of pumpjet propulsors (PJP) is addressed through a simulation-based design optimization approach built on a parametric description of the main geometrical characteristics of the system, a RANSE solver with mixing plane interface capabilities and a genetic algorithm. Both Rotor/Stator (PJP-R/S) and Stator/Rotor (PJP-S/R) configurations are considered and optimal designs from a multi-objective optimization process aimed at maximizing the propulsive efficiency at the lowest possible cavitation inception index are compared to a reference ducted propeller with decelerating nozzle (Gaggero et al., 2012), which served as baseline during the design. Detached Eddy Simulations (DES) were finally carried out to highlight, in addition to the performance improvements provided by the PJPs, also the influence of the rotor/stator/nozzle interactions on the vortical structures shed by the propulsor. Highlights: Pumpjets are efficient propulsors, especially for high-speed vessels. A pre- or a post-stator stage is used to induce pre-swirl or extract additional thrust respectively. SBDO using RANSE calculations represent a feasible design alternative for this type of propulsors. A complex interaction between blade tip vortex and vortical structures from stator and nozzle is observed using DES analyses. Such interaction has a detrimental effect on the stability of the trailing vortical wake of the propulsor.